How Vision Affects Kinematic Properties of Pantomimed Prehension Movements - Fukui, Takao; Inui, Toshio (Frontiers in Psychology, 2013)
When performing reach-to-grasp movement, the fingers open wider than the size of the target object and then stop opening. The recorded peak grip aperture (PGA) is significantly larger when performing this action without vision during the movement than with vision, presumably due to an error margin that is retained in order to avoid a collision with the object. People can also pretend such prehension action based on an internal target representation (i.e., pantomimed prehension), and previous studies showed that the kinematic differences exist between natural and pantomimed prehension. These differences are regarded as a reflection of the respective information processing in the brain, namely, the dorsal and ventral streams. Pantomimed movements are thought to be mediated by the ventral stream. This implies that visual information during the movement, which is essential for the dorsal stream, has little effect on the kinematic properties of pantomimed prehension. We investigated whether the environment’s view affects pantomimed grasping; namely, whether the dorsal stream is involved in the execution of the pantomimed action. Participants initially gazed at a target object and then were subjected to a 3-second visual occlusion, during which time the experimenter removed the object. The participants were then required to pretend reach-to-grasp movements toward the location where the object had been presented. Two visual conditions (full vision and no vision) were imposed during the pantomimed prehension by manipulating shutter goggles. The PGA showed significant differences between the two visual conditions, whereas no significant difference was noted for terminal grip aperture, which was recorded at the movement end. This suggests an involvement of the dorsal stream in pantomimed action and implies that pantomimed prehension is a good probe for revealing the mechanism of interaction between the ventral and dorsal streams, which is also linked to embodied cognition.